2019
DOI: 10.1128/jvi.01358-18
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Diversity of RNA Viruses in Australian Ticks

Abstract: Each year a growing number of individuals along the east coast of Australia experience debilitating disease following tick bites. As there is no evidence for the presence of the causative agent of Lyme disease, Borrelia burgdorferi sensu lato, in Australian ticks, the etiological basis of this disease syndrome remains controversial. To characterize the viruses associated with Australian ticks, particularly those that might be associated with mammalian infection, we performed unbiased RNA sequencing on 146 tick… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
180
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(191 citation statements)
references
References 44 publications
9
180
2
Order By: Relevance
“…RNA was extracted from ticks as described previously [33]. Briefly, ticks were washed in ethanol and homogenised in lysis buffer using a TissueRuptor (Qiagen) and RNA was extracted using the RNeasy plus mini kit (Qiagen).…”
Section: Rna Library Construction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from ticks as described previously [33]. Briefly, ticks were washed in ethanol and homogenised in lysis buffer using a TissueRuptor (Qiagen) and RNA was extracted using the RNeasy plus mini kit (Qiagen).…”
Section: Rna Library Construction and Sequencingmentioning
confidence: 99%
“…Viruses were annotated as described previously [32,33]. Viruses with full-length genomes, or incomplete genomes possessing the full-length RNA-dependant RNA polymerase (RdRp) gene, were used for phylogenetic analysis.…”
Section: Virus Genome Annotation and Phylogenetic Analysismentioning
confidence: 99%
“…Members of this group have a similar genomic structure with two ORFs spanning 3 to 4.2 kb. This group includes viruses and viral sequences described in other acarine species like the deer tick (Ixodes scapularis) and the American dog tick (Dermacentor variabilis) (Harvey et al 2019;Levin et al 2016;Levin et al 2019;Pettersson et al 2017;Sadeghi et al 2018;Shi et al 2016;Webster et al 2016) and not much information about their incidence and replication in a specific host has been reported. Nevertheless, given the mentioned similarities and the replicative activity of these viruses (see below), these V. destructor associated viruses could define a new family of +ssRNA viruses infecting invertebrates.…”
Section: New Viruses Associated To V Destructormentioning
confidence: 99%
“…Despite the importance of the ectoparasite-vector system in virus transmission and evolution, little is known about the composition of virus communities in both host types. Metagenomic studies of arthropod vector species such as mosquitoes and ticks have revealed an unexpectedly rich virus diversity, most of which likely do not infect vertebrates (Harvey, Rose, Eden, Lo, et al, 2019; Shi et al, 2017). Hence, it is not known what proportion of the viruses present in invertebrates pass to vertebrates and vice versa, although such information is central to understanding the evolution of vector-borne transmission and determining whether some viruses have more liberal host preferences than others.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of bulk RNA sequencing (“meta-transcriptomics”) has revolutionized our perception of viral diversity and host range (Shi et al, 2016; Shi, Zhang, & Holmes, 2018), revealing large numbers of seemingly benign viruses (Shi, Lin, et al, 2018). The invertebrate meta-transcriptomic studies undertaken to date include various species of ectoparasite, such as mosquitos, ticks and fleas, revealing abundant and complex viromes (Harvey, Rose, Eden, Lawrence, et al, 2019; Harvey, Rose, Eden, Lo, et al, 2019; Shi et al, 2017). Herein, by comparing the viromes of Australian wild rabbits alongside associated rabbit fleas and sympatric flies, we present the first joint study of virome composition in vertebrates and their associated ectoparasites.…”
Section: Introductionmentioning
confidence: 99%